Use of a remote piloted aircraft (RPA) to manage a building work - Arantes, Arielle Elias; Abreu, Moisés de Andrade (Brazilian Journal of Production Engineering, 2022)
Images collected with a Remotely Piloted Aircraft (ARP) can be used to detect changes and monitor the progress of a work. We sought to evaluate the potential of orthomosaics for monitoring building work. For this, 4 flights were carried out from 10/29/2021 to 12/03/2021, at 1 pm, with a Mavic 2 Pro model ARP in an enterprise located in the municipality of Eusébio-CE. The planimetric errors of the four flights ranged from 66 to 69 cm and the altimetric errors from 25 cm to 49 cm. Subsequently, in the AutoCad software, the four orthomosaics were interpreted so as to carry out the monitoring of the progress of the stages of paving, grass settlement and construction of the blocks. As a result, it was noticed that after 11/26 the paved area was below schedule, leading to delays in the other stages of the work. The Spectral Angle Difference (SAD) and Multivariate Alteration Detection (MAD) algorithms were also applied for change detection analysis, whereby both algorithms had errors greater than 40%, making the use of these algorithms impracticable to monitor the work.
Keywords: RPA; Building work; Cartographic Precision; Change Detection